Axial plunger pump for sea water desalination - DAI YUNCHAO (2016)
The invention discloses an axial plunger pump for sea water desalination. The axial plunger pump comprises a rhombus valve, a high-pressure safety valve, a low-pressure overflow valve, an oil port B, a spindle, a motor tilting tray, a plunger assembly, a rotor, a rotor lining plate, an oil distribution disc, a back cover, an oil port A and a pile-up valve. The axial plunger pump is characterized in that the rhombus valve and the low-pressure overflow valve are arranged on the left side of the spindle direction of a pump shell body, the high-pressure safety valve is arranged at the front end of the pump shell body, and the oil distribution disc is connected with the rotor through the rotor lining plate; the plunger assembly is arranged between the rotor and the motor titling tray, and the spindle and the motor titling tray are connected; the oil port A is formed in the back cover of a pump body, and the oil port B is formed between the oil distribution disc and the low-pressure overflow valve. 种海水淡化轴向柱塞泵包括菱形阀、